Karakteristik dan Keberagaman Nilai-Nilai Islami di Kampung Kauman Semarang dan Kampung Arab Sugihwaras Pekalongan - Fahmi Syarif Hidayat; Suzanna Ratih Sari (Universitas Islam Sultan Agung Semarang, 2022)
ABSTRACTIslam entered Indonesia and acculturated with local culture until forming an integration of architectural elements in each region. This study aims to identify and understand the characteristics, similarity and diversity in areas that have strong Islamic values. The method used in this research is descriptive analytical by revealing facts objectively. The selection of locus was Kauman Village Semarang because it was a Javanese settlement where the majority adhered to Islam, and Sugihwaras Arabic Village Sugihwaras, an Arab-Javanese acculturation settlement, which has architectural characteristics. Field surveys and interviews were conducted to obtain primary data, while secondary data were in the form of regional maps and literature reviews as well as previous research obtained from the Internet. From the analysis, it concluded that the characteristics and similarities are the application of the Hablumminallah value, the Hablumminannas value, and the Hablumminalalamien value. Diversity is found in the concept of spatial settlements.Keywords: Characteristics; Diversity; Islamic Values, Kauman Village, Sugihwaras Village ABSTRAK Agama Islam masuk ke Indonesia dan berakulturasi dengan budaya setempat hingga terjadi penggabungan elemen arsitektur pada masing-masing daerah. Penelitian ini bertujuan mengidentifikasi dan memahami karakteristik, keseragaman serta keberagaman pada kawasan yang memiliki nilai Islam kuat. Metode penelitian yang digunakan adalah deskriptif analitis dengan mengungkapkan fakta secara obyektif. Pemilihan lokus penelitian Kampung Kauman Semarang karena merupakan permukiman Jawa yang mayoritas menganut agama Islam, dan Kampung Arab Sugihwaras permukiman akulturasi Arab-Jawa yang mempunyai kekhasan arsitektur. Survey lapangan dan wawancara dengan narasumber dilakukan untuk mendapatkan data primer, sedangkan data sekunder berupa peta kawasan dan kajian pustaka serta penelitian terdahulu yang didapatkan dari Internet. Dari analisa didapatkan kesimpulan karakteristik dan persamaan adalah penerapan nilai Hablumminallah, nilai Hablumminannas nilai Hablumminalalamien. Keragaman terdapat pada konsep tata ruang permukiman.Kata kunci: karakteristik, keragaman, nilai Islam, Kampung Kauman, Kampung Sugihwaras